The Evaluation of Curriculum Implementation on Islamic Higher Education in Indonesia - Rohmad Qomari (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2016)
Along with the development of social culture science and technology, the curriculum in educational institution is required to be dynamic. The development of society and education have dialectical relation. The society want education role. On the other hand, the education can produce works which affect the society development. The evaluation of curriculum on higher education is very important to increase the quality process and learning outcome on higher education. One of the curriculum evaluation models which is chosen is CIPP (Context, Input, Process, and Product) evaluation model. Base on four curriculum evaluation dimension, the evaluation of curriculum implementation on higher education focused on: lecturer, higher student, lectures, and learning facilities. The result of curriculum evaluation implementation can be recommended for curriculum improvement and revision, partially or entirely.